O gesto como imagem e a imagem como gesto: a gestualidade das mãos na comunicação - Romero, Elisabeth Leone Gandini (2009)
The goal of this work is to investigate hand gestures in both communication and culture. It also aims to understand the gesture as image, analyzing some hand gestures in Image History. There are genetic and social-cultural codes interlaced in hand movements. Consequently, there is no way not to take them into account, for hands incorporate everything they reach for and everything that reaches for them too. This study embraces some aspects of gesture phylogeny due to the fact that mankind has its roots lost in time. Supported by recent etiologists researches, it confirms that no abyss separates man from other primates, and there are only common distinctions among species. Free hands encompass a true body revolution as well as a revolution in man s communication. In partnership with the brain, man faces material challenges with his technical gestures as well as with his psychological survival gestures present in culture. Gesture and image are mediators and both have their point of origin in the body. Therefore, this work privileges the primary media, but it also scopes secondary media. It shows the abundant hand gesture testimony present in cult images, art images and media images (Belting). The analysis of this corpus through Culture Semiotics Theory allows us to delineate an approach into hand gesture through some of its images: in communication and culture, ontogeny and phylogeny. Therefore the research supports itself on methodological resources developed by Ivan Bystrina, Harry Pross, Edgar Morin, Hans Belting, Régis Debray. It also articulates a dialogue with ideas and thoughts that come from the work of Ashley Montagu, Boris Cyrulnik, Eibl-Eibesfeldt, among other specialists in Communication Theory, Image Theory, Media Theory and Culture Theory